Plan estratégico para mejorar la gestión administrativa y toma de decisiones de la Cooperativa de Ahorro y Crédito “El Migrante Solidario" - Ortiz Alvarado, Tania Jovita (2014)
The growth of a business depends on many factors, it is especially important to have an effective administrative management in making correct decisions. Considering all these aspects research on corporate governance on all that has to do with the administrative field of Cooperative Savings and Credit "The Migrant Solidarity" that provides financial services in Biblián City, Province of Cañar, is done this institution Cooperative Financial System has a few years on the market and what it has done is kept against stiff competition, making it necessary that its shortcomings are identified and their potential, delivering end an operating plan that allows growth in the next two years, as long as the partners and directors of the company have the firm intention to join forces to put aside what they are doing wrong, strengthen what they are doing well and accept suggestions to set out on new paths in the field of financial institutions.